2002
DOI: 10.1258/0022215021909935
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegrated implants in the management of childhood ear abnormalities: with particular emphasis on complications

Abstract: Little has been published about the difficulties encountered during the insertion of osseointegrated implants for the attachment of bone anchored hearing aids (BAHA) and auricular prostheses in children. This study examines this issue in the first 51 children implanted at our centre. During surgery, the most common problem encountered was the presence of thin bone resulting in incomplete insertion of fixtures. Five fixtures had failed to integrate and six fixtures were lost in the long-term, however, only five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 10 publications
1
64
0
3
Order By: Relevance
“…In a comparable paediatric study the one stage technique was found to be safe and effective with a low complication rate [6]. In other paediatric series with two-stage implantation 5-10% of implants failed to osseointegrate [10,11] and late fixture loss occurred in 9-10% [12,13]. Thus, although the two-stage procedure also has a low complication rate, the single stage is more favourable since a second anaesthetic can be avoided in this group.…”
Section: Discussionmentioning
confidence: 84%
“…In a comparable paediatric study the one stage technique was found to be safe and effective with a low complication rate [6]. In other paediatric series with two-stage implantation 5-10% of implants failed to osseointegrate [10,11] and late fixture loss occurred in 9-10% [12,13]. Thus, although the two-stage procedure also has a low complication rate, the single stage is more favourable since a second anaesthetic can be avoided in this group.…”
Section: Discussionmentioning
confidence: 84%
“…This shows that the implant does not interfere with the bony skull growth. Most our patients (63.6 %) had two stage surgeries Some authors even advocate the implantation of sleepers that is more than one titanium fixture implant in cases of probable failed osseointegration [9,10]. There was only one patient where we put sleeper.…”
Section: Discussionmentioning
confidence: 91%
“…Yellon and only limited complications. Other groups have reported similar results in children [1][2][3][4][5][6]. The conclusions of this study are limited by the small number of patients and relatively short follow up period.…”
Section: Discussionmentioning
confidence: 48%
“…Although there is no prospective study, anecdotal reports (A. Tjellstrom, MD, PhD, personal communication 2005) suggest that a longer period (at least 6 months) between the two stage procedures allows for adequate osseointegration. The need for revision surgery for replacement of lost fixtures may be reduced by placement of a second ''sleeper'' fixture at the time of initial surgery that may be used if the primary fixture fails to osseointegrate [5]. Sleepers were not placed in this group of patients.…”
Section: Discussionmentioning
confidence: 99%